Indonesian Interference in the Students’ Writing of Recount Text at SMA Negeri 1 Toma - Rika Purnama Sari; Rahmat Gaho (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
The obejctives of this research is two-fold: to describe how Indonesian language interferes the recount text written by students of SMA Negeri 1 Toma and to identify the types of Indonesian interferences in recount texts written by Students in question. The design of this research is qualitative. Data of the research were analysed using the qualitative data analysis technique of Miles et al. (2014). The data in this research were recount text written by students of SMA Negeri 1 Toma and semistructure interview taken from the students in SMA Negeri 1 Toma. Results show Indonesian language system interfered the recount texts written by students of SMA Negeri 1 Toma in that the students adopted the way of Indonesian words, phrases, and sentences are structured. The types of Indonesian interference occur in recount text written by students of SMA Negeri 1 Toma distinguished into morphological, syntactical and semantic. Therefore, it can be concluded that students adopted the way of Indonesian words, phrases, and sentences are structured because they do not master Indonesian or L2 and English or L3 most in structuring the phrases and sentences. The teaching of English to non-English speaking people should take into account the highlights of the differences between English and Indonesian linguistic system.